PERBANDINGAN SUHU LINGKUNGAN DAN PRODUKTIVITAS TERNAK SAPI PERAH MELALUI PENDEKATAAN STOCHASTIC FRONTIER (Study Kasus di Peternakan Rakyat KUTT Suka Makmur): Comparison Of Environment Temperature and Dairy Cattle Productivity Approach a Stochastic Frontier (Case Studyin Small Holder Dairy Farms KUTT Suka Makmur) - Harini, Dela; Purwanto, Bagus Priyo; Suryahadi (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2016)
This study observed environmental temperature and rearing management of dairy cattlein KUTT Suka Makmur. This research was aimed to evaluate comparison of environment temperature, productivity, and the technic inefficiency dairy cattle in lowland and highland. Datacollected from 40 respondents in lowland and 40 respondents in highland regions. Data analyzed using descriptive statistics and stochastic frontier production. The results showed that temperatures in the lolands were higher than that of highland, at the range of 24-27 oC, socattle experiencing heat stress, the impact was cattle consumedless feed. In contrast, the highlands temperature relatively low, at range of22-24 oC and produce more milk than that of lowland. The significant variabel of stochastic frontier was herd size about -0.2655 (p